Surgery Treatment of Primary Tumors of the Inferior Vena Cava - Wang, Shizhi; Li, Yuqiu; Yang, Qijun; Zhang, Xue; Cheng, Yunqi; Li, Zimeng; Wang, Jingyi; Zeng, Qingfu (Frontiers in Medicine, 2022)
Background: Primary tumor of the inferior vena cava is a rare tumor, which arises from the smooth muscle of vascular walls. Surgery appears the only curative treatment. However, the optimal surgical methods and surgical management are not well studied. In this article, we reviewed the successful treatment experience of patients in our center who had resection of primary tumor of the inferior vena cava and reviewed the relevant literature. Methods: Four cases of patients who underwent initial resection of primary tumors of the inferior vena cava from September 2017 to August 2021 in the Second Affiliated Hospital of Nanchang University were screened and followed up. They were discussed and cases reported in this field were reviewed. Results: Among the four patients, three of them were female. The median age of the disease is 53.75 years (range 45-60 years). After surgical treatment, tumors were removed in all patients, and some patients had reconstruction of inferior vena cava. There were no disease-specific deaths, no serious complications, and no recurrence during follow-up in these cases. Conclusions: Careful preoperative examination, correct surgical treatment methods, and multidisciplinary collaboration can lead to safe and successful operations, which improve the survival rate of patients.